2018
DOI: 10.1038/s41598-018-20334-z
|View full text |Cite
|
Sign up to set email alerts
|

Strain-engineered two-dimensional MoS2 as anode material for performance enhancement of Li/Na-ion batteries

Abstract: Recent years have witnessed a surge of research in two-dimensional (2D) nanostructures for development of new rechargeable Li/Na-ion battery systems. Herein, via first-principles calculations we demonstrate strain-engineered Li/Na adsorption and storage in 2D MoS2 as anode material, aiming to enhance the operating performance of Li/Na-ion batteries. Our results show that tensile strain greatly increases the adsorption of Li/Na atoms on MoS2, and a modest strain of 6% increases Li (Na) adsorption energy by over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 64 publications
3
34
0
Order By: Relevance
“…In Figures 4A,B , the band gap of MoS 2 was seen to vanish during the adsorption of Li and Na-ions in contrast to the existence of the band gap in the adsorption of Mg and Zn-ions on MoS 2 . For comparison, the DOS of pure MoS 2 had be repeated ( Figure 5 ), which was in accordance with the reported previously (Hao et al, 2018 ; Chen et al, 2020 ). These results indicated that the semiconductor MoS 2 may be transformed into metal during the insertion of Li and Na ions, while the properties of the MoS 2 semiconductor remained unchanged during the insertion of Mg and Zn ions ( Figure 4D ), resulting in low electronic conductivity in divalent-ions batteries.…”
Section: Resultssupporting
confidence: 89%
“…In Figures 4A,B , the band gap of MoS 2 was seen to vanish during the adsorption of Li and Na-ions in contrast to the existence of the band gap in the adsorption of Mg and Zn-ions on MoS 2 . For comparison, the DOS of pure MoS 2 had be repeated ( Figure 5 ), which was in accordance with the reported previously (Hao et al, 2018 ; Chen et al, 2020 ). These results indicated that the semiconductor MoS 2 may be transformed into metal during the insertion of Li and Na ions, while the properties of the MoS 2 semiconductor remained unchanged during the insertion of Mg and Zn ions ( Figure 4D ), resulting in low electronic conductivity in divalent-ions batteries.…”
Section: Resultssupporting
confidence: 89%
“…It is noted that the adsorption energies on the surface of so‐MoS 2 are significantly higher in comparison to the h‐MoS 2 surface that makes so‐MoS 2 potentially better for application as anodes in LIBs/SIBs. [ 60,61 ] The stronger adsorption energies lead to a rapid loading process with an exothermic reaction between Li/Na and so‐MoS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In the extreme case of interlayer expansion, some 2D materials, including graphene and MoS 2 , become thermodynamically unstable upon Li adsorption, resulting in the irreversible formation of Li metal clusters. [17][18][19] To overcome such a limitation, surface defects in 2D layers have been demonstrated as an effective way to enhance the thermodynamic stability of both graphene and TMD monolayers, contributed by increased charge transfer. [20][21][22][23] Unfortunately, such a defect engineering method is highly limited by its uncontrollable synthesis procedure and undesired mechanical failure upon lithiation.…”
Section: Introductionmentioning
confidence: 99%